Depolymerization of waste polyethylene to linear alkenes via sequential dehydrogenation and metathesis - Khopade, Kishor V.; Rajput, Nikhita S.; Rangappa, Raghavendrakumar; Barsu, Nagaraju; Chikkali, Samir H. (Green Chemistry, 2024)
Polyethylene (PE) is the most abundantly sourced plastic and significant efforts are needed for its end-of-life management. The deconstruction of PE is an uphill task and requires the breaking of highly stable C-C bonds. Here we demonstrate that PE can be deconstructed to value-added dodecene, along with other long-chain alkenes. The PCP-iridium complex catalyzes the dehydrogenation of commercial and post-consumer polyethylene waste to produce dehydrogenated polyethylene (DHP) with 0.5-1.0% unsaturation. The DHP was subjected to an ethylene cross-metathesis reaction in the presence of suitable catalysts. Through meticulous optimization of reaction parameters, 63% selectivity toward dodecene, with 26% overall yield, was achieved. The practical significance of our method has been demonstrated by subjecting post-consumer plastic waste to dehydrogenation followed by ethylene metathesis to produce dodecene as a major product, together with long-chain alkenes. The PE deconstruction has been confirmed by recording molar mass before and after depolymerization using high-temperature gel permeation chromatography. The existence of dodecene has been unambiguously ascertained using GC, GC-MS, NMR, and IR spectroscopy. Thus, these results demonstrate the conversion of waste PE to value-added dodecene and long-chain alkenes under mild reaction conditions.

Designing of imine thiophene-ligated metal-complexes and implication in ethylene polymerization - Shaikh, Maulali H.; Ramekar, V. Rohan; Jawoor, Shailaja; Dash, Soumya R.; Birajadar, Rajkumar S.; Pawal, Sandip B.; Thenmani, Nandakumar; Vanka, Kumar; Chikkali, Samir H. (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2024)
Polyethylene is the single largest volume polymer produced globally using Ziegler-type catalysts. Numerous modifications have been reported in search of a better catalyst that can control molecular weight, polydispersity, and branching. In our attempts to identify a suitable imine thiophene-ligated chromium complex, we examined 9 different titanium complexes computationally. The DFT investigations considered barriers for insertion, propagation, and termination by beta-H elimination or chain transfer, and identified N-(4-methoxyphenyl)-2-phenyl-1-(thiophen-2-yl)ethan-1-imine(L9) as the most suitable ligand. Subsequently, L9 was prepared in good yield (70%) by condensing 2-phenyl-1-(thiophen-2-yl)ethan-1-one with 4-methoxyaniline. Ligand L9 was treated with early transition metal precursors (Ti, Cr, Zr) to generate a homogenous catalyst. The identity of these catalysts was unambiguously ascertained using a combination of NMR, ICP, FT-IR, UV-Vis spectroscopy, and ESI-MS. The performance of L9-ligated titanium complex [Cat.1] was examined in ethylene polymerization using MMAO as a co-catalyst. Insertion of ethylene was tracked using high-pressure NMR experiments and Cat.1 was found to be active in the polymerization. Ethylene polymerization conditions were optimized to obtain high activity and molecular weight polyethylene. The chromium complex [Cat.2] outperformed the Ti and Zr-derived catalysts with the highest TOF of 6294 mol of PE/mol of Cr/h. Cat.2 produced high molecular weight, high-density polyethylene.
Keywords: Cr-complexes; DFT; high-density polyethylene; Imine thiophene ligand; Polyethylene

Direct synthesis of phosphine-phosphite ligand and its implication in asymmetric hydrogenation of functionalized olefins - Chandanshive, Amol C.; Khopade, Kishor V.; Chikkali, Samir H. (Chemistryselect, 2026)
Phosphine-phosphite (P-OP) ligands constitute a privileged class of chiral ligands in asymmetric catalysis owing to their modular structures and tunable steric and electronic properties. Herein, we report a direct, one-pot, synthesis of a new flexible P-OP ligand (L) derived from BINOL-PCl and its in situ complexation with rhodium (Rh) for catalytic evaluation. The resulting Rh/L system efficiently hydrogenates a diverse library of 19 functionalized olefins under mild conditions, delivering moderate to excellent enantioselectivities, with ee values reaching up to 99%. Several of the hydrogenated products correspond to valuable chiral building blocks relevant to pharmaceutical synthesis, underscoring the practical utility of flexible P-OP ligand architectures in asymmetric hydrogenation.
Keywords: asymmetric hydrogenation; functionalized alkene; ligand design; metal catalyzed; phosphine-phosphite